Ivangustin, a sesquiterpene lactone from Inula japonica Thunb., attenuates neuroinflammation through covalent inhibition of ubiquitin-conjugating enzyme UBE2L3 - Mengyuan Qiao; Hanyue Gan; Yuying Shi; Shan Yang; Ting Liu; Xiaofei Shen; Wenbin Wu (Chinese Medicine, 2026)
Abstract Background Neuroinflammation is a key driver and an important therapeutic target of neurodegeneration. Dysregulated nuclear factor-κB (NF-κB) signaling plays a central role in neuroinflammation and depends on M1 and K63 ubiquitination of NF-κB essential modulator (NEMO). Ivangustin (IVA) is a sesquiterpene lactone isolated from Inula japonica Thunb., a traditional Chinese medicine has been used to treat inflammatory diseases. But its anti-neuroinflammatory effects and molecular targets remain unclear. Purpose This study aimed to evaluate the anti-neuroinflammatory effects of IVA and elucidate its direct functional target and underlying mechanism. Methods Integrated in vitro, in vivo, and in silico/bioinformatics approaches were employed. The anti-neuroinflammatory activity of IVA was evaluated in LPS-stimulated BV2 cells, primary microglia, and an LPS-induced acute cognitive impairment mouse model. Mechanistic studies were performed using pull-down, liquid chromatography-tandem mass spectrometry (LC–MS/MS), cellular thermal shift assay (CETSA), drug affinity responsive target stability (DARTS), gene knockdown, point mutation and bioinformatics analyses. Results In vitro, IVA significantly inhibited nitric oxide (NO) production and mRNA and protein expression of pro-inflammatory factors in LPS-stimulated microglia. Furthermore, IVA significantly suppressed inhibitor of NF-κB kinase α/β (IKKα/β) and inhibitory subunit of NF-κB alpha (IκBα) phosphorylation, IκBα degradation, and NF-κB p65 phosphorylation and nuclear translocation, thereby blocking the expression of NF-κB-targeted genes. Its anti-neuroinflammatory activity was attenuated by thiol donors, indicating the importance of its electrophilic lactone moiety. Furthermore, ubiquitin conjugating enzyme E2L3 (UBE2L3) was identified as the functional target of IVA in BV2 cells, whereas UBE2L3 knockdown markedly attenuated IVA-mediated anti-neuroinflammatory action. Bioinformatics analysis suggests UBE2L3 overexpression as a potential risk factor for neurodegenerative diseases. Mechanistically, IVA covalently bound to the catalytic cysteine 86 of UBE2L3, thereby inhibiting UBE2L3-mediated M1 and K63 ubiquitination of NEMO, which is crucial for NF-κB activation. In vivo, IVA ameliorated LPS-induced cognitive impairment and neuroinflammation in mice via inhibiting Iba1 expression and suppressing NF-κB activation. Conclusion IVA exerts anti-neuroinflammatory effects by covalently targeting UBE2L3 and suppressing NF-κB signaling. These findings also identify UBE2L3 as a potential therapeutic target for neuroinflammation and support IVA as a promising lead compound for further preclinical investigation of neuroinflammatory disorders.